Pengaruh Kedisiplinan Belajar Terhadap Hasil Belajar Matematika Siswa Kelas VII SMP Negeri 3 Baubau - Sardin Sardin; Basri Naenu (Jurnal Akademik Pendidikan Matematika, 2021)
This research aimed to determine the significant positive effect of learning discipline on the mathematics learning outcomes of seventh grade students at SMP Negeri 3 Baubau. This research used ex post facto method whit quantitative research type. The population in this research were all seventh grade student at SMP Negeri 3 Baubau which consisted 8 classes whit a total of 243 students. While the sample in this research war 35% of the population or as many as 85. Data collection using questionnaires and documentation. The data analysis technique used prerequisite test, with simple correlation and regression analysis. Hypothesis testing technique using regression analysis. Sourced from the results of data analysis and a simple regression estimate of disciplinary assessment (X) on learning outcomes (Y) resulted in a significance value of 0.036 < 0.05. So that it could be concluded that there was an influence of discipline (independents variable) on learning outcomes (bound variable). SPSS output results also produce R2 was 0.052. this showed the magnitude of the influence of discipline on learning outcomes was a much as 5.2%. According to the equation of the formulation of a simple regression analysis was Y = 53.029 + 0.164X, it could be seen that the discipline variable at the 1% level was better, the student learning outcomes would increase by 0.164. Thus, based on the hypothesis that could be taken, there was a significant positive effect of learning discipline on the mathematics learning outcomes of seventh grade student at SMP Negeri 3 Baubau